Adab Education Management in Islamic Boarding School: A Case Study - Shafwan, Muhammad Hambal; Suprapto, Suprapto (IKIP PGRI Bojonegoro, 2025)
This research aims to discuss how to manage adab education at the TQH al-Hasyimi Tenggulun Solokuro Lamongan Islamic Boarding School. is qualitative research with a case study approach, which means this research is carried out in a natural context to understand the phenomena that occur. The methods used include various techniques to carry out in-depth interpretation of the phenomenon. The results of this research explain that adab education at the TQH al-Hasyimi Islamic boarding school uses the book